2009
DOI: 10.1080/08858190802665245
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cervical Cancer Education for Deaf Women Using a Video Educational Tool Employing American Sign Language, Open Captioning, and Graphics

Abstract: Background Deaf women encounter barriers to accessing cancer information. In this study, we evaluated whether deaf women's knowledge could be increased by viewing a graphically enriched, American Sign Language (ASL) cervical cancer education video. Methods A blind, randomized trial evaluated knowledge gain and retention. Deaf women (n = 130) completed questionnaires before, after, and 2 months after viewing the video. Results With only a single viewing of the in-depth video, the experimental group gained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 28 publications
(17 reference statements)
4
33
0
Order By: Relevance
“…However, these improvements in cervical cancer healthcare require knowledge of cervical cancer and screening. Deaf women face greater barriers to accessing health information and healthcare than hearing women, which places them at higher risk of decreased screening, later detection, and increased morbidity and mortality [24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these improvements in cervical cancer healthcare require knowledge of cervical cancer and screening. Deaf women face greater barriers to accessing health information and healthcare than hearing women, which places them at higher risk of decreased screening, later detection, and increased morbidity and mortality [24]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, in one sample of Deaf women, 37% reported that they had no knowledge of cervical cancer [1]. Lack of knowledge has been associated with decreased screening and early detection rates, suggesting that Deaf women may be at a higher risk of discovering late stage cervical cancer and hence, at higher risk for needing more aggressive treatments and having higher rates of mortality [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Though none have addressed genetic predispositions, efforts that address language-concordance by accounting for ASL as the first language for many deaf individuals have been found to increase their knowledge regarding a variety of cancers (3-8, 25, 26) and to promote cancer screening behaviors (6). Although conveying health information in ASL is key, these efforts also have included visual images and graphics and English language elements such as captioning or English text.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of culturally and linguistically sensitive approaches for providing health care has been shown to increase health knowledge in the deaf population regarding tobacco-related diseases (Berman et al 2011) and cervical cancer (Choe et al 2009), and to produce significant increases in understanding of prostate and testicular cancer that remained present two months after receipt of information (Folkins et al 2005). …”
Section: Introductionmentioning
confidence: 99%